Reversible Manipulation of Photoconductivity Caused by Surface Oxygen Vacancies in Perovskite Stannates with Ultraviolet Light (Adv. Mater. 5/2022). Issue 5 (3rd February 2022) - Lee, Yujeong; Yoon, Daseob; Yu, Sangbae; Sim, Hyeji; Park, Yunkyu; Nam, Yeon‐Seo; Kim, Ki‐Jeong; Choi, Si‐Young; Kang, Youngho; Son, Junwoo
Abstract : 2D Photoconductivity Light–matter interaction under different oxygen pressures can reversibly manipulate photoconductivity from surface oxygen vacancies of perovskite stannate semiconductors. In article number 2107650, utilizing a surface‐selective photochemical reaction, Junwoo Son and co‐workers report that ultraviolet‐excited electron–hole pairs of a perovskite compound under low oxygen pressure accelerate the unprecedented formation of spatially confined and optically programmable in‐gap states induced by oxygen vacancies at room temperature.